Educação em tempo integral nas escolas municipais de Vitorino/PR: uma análise da educação ambiental no ensino fundamental - Tomassoni, Fernanda (2024)
This study was accomplished at the José Bonifacio Municipal School in the city of Vitorino/PR. The aim of the study was to analyze full-time education at the José Bonifacio Municipal School, looking at the environmental education perspective, in order to propose a Model Curriculum Matrix for Full-Time Education for Elementary School - Early Years, adding the environmental theme in an integrated way and considering the municipality's potential. The guiding instruments for education in Brazil were used as a basis, as were those focused on the environment, the Environmental Education Projects already implemented in Brazilian schools, the Pedagogical Political Project of the José Bonifacio Municipal School and other models related to the subject. The stages of the research were a bibliographical survey, the application of a questionnaire to the participants, seeking to identify the knowledge of those involved on the subject studied, the analysis of the institution's Pedagogical Political Project and finally the preparation of the Proposal. Teaching and learning are two processes related to education, which is responsible for changes and developments in society. Educating is not only important, it is also possible, in order to strengthen the bonds of citizenship, inserting the subject into decisions that benefit society, forming an autonomous citizen. The Full-Time School is an innovative pedagogical proposal in which students' time at school is extended, offering a flexible curriculum. The inclusion of Environmental Education in an integrated and interdisciplinary, continuous and permanent way in all phases, stages, levels and modalities of education, contributes to the promotion of rationality and preservation of the environment, leading to sustainability. The proposed Curriculum Matrix Model is not intended to exhaust the subject or impose the idea categorically, but rather to serve as a starting point for other models.